Imagination and Conscience in the conversion of J. H. Newman - Pérez Alcalá, Fernando (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
This article seeks to present how original, deep and actual is the conversion of John Henry Newman. Based on some of his writings, this approach demonstrates how his road towards Catholicism was a balanced combination of imagination, intellectual enterprise and accomplishment of a duty of conscience.